Stress corrosion cracking in Type.316 plates of a heat exchanger. (April 2016) - Khodamorad, S.H.; Alinezhad, N.; Haghshenas Fatmehsari, D.; Ghahtan, K.
Highlights: The chloride ions build-up in crevices at high temperature is the main reason of SCC. The suspended soil of water settles in the crevices and provides a suitable dead zone. The pitting corrosion under gasket seat occurs and acts as start point of SCC. Abstract: In Jam petrochemical complex (JPC), Iran, the plates (ASTM A.240 Type.316) of some heat exchangers have been damaged due to the occurrence of cracks at the sitting place of gaskets. A comprehensive failure analysis including the chemical analysis, visual inspection, optical microscopy and scanning electron microscopy (SEM) of the cracks spread over the plates together with the energy dispersive X-ray spectroscopy (EDS) of the corrosion products and the measurement of chloride and sulfide ions content of the process water were employed for the examination of the failure mode and its causes. The obtained results indicate the building-up of the chloride and sulfide ions at the crevices between plates and gaskets at high temperature leads to stress cracking corrosion (SCC) of the plates. Moreover, the simultaneous presence of chloride and sulfide in the media hastens the SCC failure in the heat exchanger plates.